PARP inhibitors in the treatment of Pancreatic Cancer - A Review of literature - Jagoda Niewiadomska; Wiktor Grela; Daria Furtak; Dawid Tulej; Paulina Głogowska; Alicja Dziedzic; Natalia Gniaź; Dominika Marciniuk; Natalia Marko; Aleksandra Górska (Journal of Education, Health and Sport)
Introduction